Loneliness and Social Media Addiction Tendencies among Young Adult Men in Real and Cyberspace Worlds - Syiva Rizkya; Ayunda Ramadhani; Aulia Suhesty; Aulia Ramdhani (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
This study aims to examine the relationship between loneliness and social media addiction tendencies among early adult males (18–25 years old). Additionally, it explores how social media is used as a compensation for unmet social and emotional needs. The research employed a quantitative correlational design with purposive sampling of early adult male participants. The results revealed a strong and significant positive correlation between loneliness and social media addiction (r = 0.635; p < 0.05). These findings indicate that higher levels of loneliness are associated with greater tendencies toward social media addiction. This study reinforces the Need-satisfaction theory and highlights the importance of interventions aimed at reducing loneliness to prevent social media addiction Keywords: early adult males, loneliness, need-satisfaction, social compensation, social media addiction.